الفائض الاقتصادي الصناعي في العراق: تحديات وحلول - محمد، هبة أحمد; الحجيمي، سهيلة (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2022)
أولى البحث الاهتمام المتزايد بموضوع الفائض الاقتصادي الصناعي بوصفه أحد مكونات النمو الصناعي وآلياته وخاصة في البلدان النامية، وإن سلوكية الفائض الصناعي سواء في البلدان المتقدمة أو النامية سيعطى مؤشرا اقتصاديا مهما عن اتجاه التنمية الاقتصادية فيها لذلك استهدف البحث دراسة قيمة الفائض الاقتصادي الصناعي في العراق لمعالجة العديد من التحديات منها الاعتماد على الإيرادات النفطية وتراجع أسعاره، وبهدف تنويع مصادر الدخل الوطني في العراق، وللنهوض بالقطاع الصناعي وتحديد الآثار التي يمكن أن يحدثها الفائض الاقتصادي الصناعي في معدل النمو الاقتصادي للعراق وقد تم اختيار المدة 2004-2018، من خلال البحث تم التوصل إلى نتيجة مفادها أن أوضاع الصناعة في العراق متواضعة إلى حد كبير، وذلك لعدم الاهتمام بالقطاع الصناعي وإهمال عنصر. التغير التكنولوجي، مما يخفض من الفائض الصناعي المحتسب كما أن الصناعة التقليدية تعمل على تخفيض تحصيل رأس المال مما يترتب عليه تدني إيراداتها، مما يؤدي إلى تسرب الفائض الاقتصادي بعيدا عن مساعي النمو الصناعي. The research paid increasing attention to the issue of the industrial economic surplus as one of the components of industrial growth and its mechanisms, especially in developing countries, and that the behavior of the industrial surplus, whether in developed or developing countries, would give an important economic indicator about the direction of economic development in them, so the research aimed to study the value of the industrial economic surplus in Iraq to address many Among the challenges are dependence on oil revenues and the decline in its prices, with the aim of diversifying the sources of national income in Iraq, and for the advancement of the industrial sector, and to determine the effects that the industrial economic surplus can have on the economic growth rate of Iraq, which was chosen for the period 2004-2018. Through the research, a result was reached. The effect that the conditions of the industry in Iraq are modest to a large extent, due to the lack of interest in the industrial sector and the neglect of the element of technological change, which reduces the calculated industrial surplus, and the traditional industry is working to reduce the collection of capital, which results in a decline in its revenues, which leads to the leakage of the economic surplus away. for industrial growth endeavors.
Keywords: التنمية الاقتصادية -- الزيادة الإنتاجية -- الإيرادات الصناعية -- القطاع النفطي -- مصادر الدخل -- العراق